2007
DOI: 10.1525/sop.2007.50.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Effects on Youth Substance Use in a Southwestern City

Abstract: This study examines neighborhood influences on alcohol, cigarette and marijuana use among a predominantly Latino middle school sample. Drawing on theories of immigrant adaptation and segmented assimilation, we test whether neighborhood immigrant, ethnic, and socioeconomic composition, violent crime, residential instability, and family structure have differential effects on substance use among youth from different ethnic and acculturation backgrounds. Data are drawn from self-reports from 3,721 7 th grade stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 79 publications
(118 reference statements)
3
70
0
Order By: Relevance
“…The elevated risk for smoking in First Nations communities and other Aboriginal communities was accounted for by perceived community social problems. This finding is consistent with previous findings among nonAboriginal populations which have reported increased rates of substance use 12,13 in high crime neighbourhoods.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The elevated risk for smoking in First Nations communities and other Aboriginal communities was accounted for by perceived community social problems. This finding is consistent with previous findings among nonAboriginal populations which have reported increased rates of substance use 12,13 in high crime neighbourhoods.…”
Section: Discussionsupporting
confidence: 93%
“…ii) high crime neighbourhoods are associated with increased rates of substance use; 12,13 and iii) community SES disadvantage is linked to increased risk for smoking. [14][15][16] However, evidence for the association between community SES and alcohol use is mixed.…”
mentioning
confidence: 99%
“…In contrast, other studies have found no support for the disadvantage hypothesis and substance use, 25 and still other studies have shown mixed results depending on the measure of neighborhood socioeconomic status 26 or the outcome examined. 27,28 Karriker and colleagues 29 found neighborhood disadvantage was associated with elevated risk of negative drinking consequences, particularly for White women and African American men but not to alcohol dependence symptoms. Although prior studies have examined neighborhood influences on drinking behavior, few studies have used large, nationally representative samples or examined different dimensions of neighborhood disadvantage or multiple outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Most relevant to the current study, prior research has consistently found a link between neighborhood violence and increased levels of substance use (Vermeiren, AGGRESSION AND SUBSTANCE USE IN HISPANICS Schwab-Stone, Deboutte, Leckman, & Ruchkin, 2003;Winstanley et al, 2008). For example, Kulis, Marsiglia, Sicotte, and Nieri (2007) found disadvantaged neighborhoods, where poverty and crime is prevalent, to be associated with increased substance use in Latino middle school youths.…”
Section: The Impact Of Neighborhood Violencementioning
confidence: 64%